2006
DOI: 10.1037/0022-3514.90.3.468
|View full text |Cite
|
Sign up to set email alerts
|

Sex similarities and differences in preferences for short-term mates: What, whether, and why.

Abstract: Are there sex differences in criteria for sexual relationships? The answer depends on what question a researcher asks. Data suggest that, whereas the sexes differ in whether they will enter short-term sexual relationships, they are more similar in what they prioritize in partners for such relationships. However, additional data and context of other findings and theory suggest different underlying reasons. In Studies 1 and 2, men and women were given varying "mate budgets" to design short-term mates and were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
494
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 590 publications
(538 citation statements)
references
References 80 publications
(181 reference statements)
38
494
1
5
Order By: Relevance
“…In general, these theories imply that motivational states are conditioned through adaptation and thus create attentional biases towards increasing reproductive opportunities (Maner et al 2007). It has been strongly suggested that attention is specifically directed at individuals of the opposite sex with evolutionarily attractive qualities (young in appearance, fertilelooking, symmetrical, etc) or to other physically attractive members of the same sex who are considered threats or "intrasexual competition" (Li and Kenrick 2006;Maner et al 2003Maner et al , 2007. Therefore, these evolutionary theories of attention explain our findings that young participants are significantly more attentive to other young attractive faces.…”
Section: Discussionmentioning
confidence: 99%
“…In general, these theories imply that motivational states are conditioned through adaptation and thus create attentional biases towards increasing reproductive opportunities (Maner et al 2007). It has been strongly suggested that attention is specifically directed at individuals of the opposite sex with evolutionarily attractive qualities (young in appearance, fertilelooking, symmetrical, etc) or to other physically attractive members of the same sex who are considered threats or "intrasexual competition" (Li and Kenrick 2006;Maner et al 2003Maner et al , 2007. Therefore, these evolutionary theories of attention explain our findings that young participants are significantly more attentive to other young attractive faces.…”
Section: Discussionmentioning
confidence: 99%
“…At one extreme, researchers have focused on shortterm, casual sexual relationships between relatively unacquainted individuals like the ''one-night stand'' (Cubbins & Tanfer, 2000;Li & Kenrick, 2006), the ''hookup'' (Paul et al, 2000), and the ''chance encounter'' (Fisher & Bryne, 1978). At the other extreme, researchers have studied long-term, committed relationships, most exemplified by marriage (Buss, 1989b;Christopher & Sprecher, 2000).…”
Section: A Compromise Between Ideals In Relationshipsmentioning
confidence: 99%
“…The good genes traits that relate especially positively to short-term attractiveness tend to be physical features, especially testosterone-linked traits such as relatively masculine body, face, and voice (Li & Kenrick, 2006;Little, Connely, Feinberg, Jones, & Roberts, 2011;Lucas, Koff, Grossmith, & Migliorini, 2011;Pawlowski & Jasienska, 2005;Provost, Kormos, Kosakoski, & Quinsey, 2006;Puts, 2010). With regard to bodily traits specifically, V-shaped upper body and features indicating muscularity, strength, and physical fitness have been found to be more important in short-term than in long-term contexts (Braun & Bryan, 2006;Li & Kenrick, 2006;Little et al, 2011;Lucas et al, 2011). In contrast, traits that are especially predictive of long-term attractiveness tend to relate more to parental investment, such as social status, access to resources, and the ability to provide protection (Buss & Schmitt, 1993;Li, 2007;Li & Kenrick, 2006).…”
Section: Fitness Protection Ability and Evolutionary Perspectivesmentioning
confidence: 99%
“…With regard to bodily traits specifically, V-shaped upper body and features indicating muscularity, strength, and physical fitness have been found to be more important in short-term than in long-term contexts (Braun & Bryan, 2006;Li & Kenrick, 2006;Little et al, 2011;Lucas et al, 2011). In contrast, traits that are especially predictive of long-term attractiveness tend to relate more to parental investment, such as social status, access to resources, and the ability to provide protection (Buss & Schmitt, 1993;Li, 2007;Li & Kenrick, 2006). In summary, perceptions of physical traits indicating masculinity and formidability (i.e., dominance) and fitness are hypothesized to mediate the link between WCR and short-term attractiveness, and traits indicating the ability to provide investment and protection are hypothesized to mediate the link between WCR and long-term attractiveness.…”
Section: Fitness Protection Ability and Evolutionary Perspectivesmentioning
confidence: 99%